2021
DOI: 10.1055/s-0041-1726103
|View full text |Cite
|
Sign up to set email alerts
|

Searching the PDF Haystack: Automated Knowledge Discovery in Scanned EHR Documents

Abstract: Background Clinicians express concern that they may be unaware of important information contained in voluminous scanned and other outside documents contained in electronic health records (EHRs). An example is “unrecognized EHR risk factor information,” defined as risk factors for heritable cancer that exist within a patient's EHR but are not known by current treating providers. In a related study using manual EHR chart review, we found that half of the women whose EHR contained risk factor information meet cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…38 Since electronic health records (EHRs) contain more and more data, researchers develop methods to extract characteristics either from data 39 40 or scanned and other outside documents contained in EHRs. 41 In the market, data management systems available clinical, such as REDCap, OpenClinica, and eClinicalOS, but these systems are either commercial or not suitable for this project because the whole workflow is time consuming, error prone, and requires the integration of different components.…”
Section: Discussionmentioning
confidence: 99%
“…38 Since electronic health records (EHRs) contain more and more data, researchers develop methods to extract characteristics either from data 39 40 or scanned and other outside documents contained in EHRs. 41 In the market, data management systems available clinical, such as REDCap, OpenClinica, and eClinicalOS, but these systems are either commercial or not suitable for this project because the whole workflow is time consuming, error prone, and requires the integration of different components.…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural language processing (NLP) models to extract data from unstructured free text in the electronic health record (EHR) has demonstrated efficiency and potential to reduce missed clinically significant information compared with manual review. 10,11 The complete methodology is described in a manuscript detailing the development of our NLP model to classify the authorship of PSMs. 12 In brief, we trained an NLP model on a dataset of 1,850 individual messages with manual annotation of patient or presumed proxy as our gold standard in concordance with other NLP models categorizing PSMs.…”
Section: Background and Significancementioning
confidence: 99%
“…The participants suggested that in the future it would be ideal if one could take a photograph of their child's prior vaccine record with their phone's camera, upload the photograph into the Immunize PediatricTransplant app, and then have the app automatically recognize vaccine names and dates. Optimal character recognition with natural language processing has recently been shown to have the potential to accurately identify clinically relevant information contained within the EMR [44][45][46][47].…”
Section: Principal Findingsmentioning
confidence: 99%